Automated Dynamic Service Placement And Replication Framework Using Team Formation Approach To Enhance Service Availability - Ooi, Boon Yaik (2012)
Managing and administering services in the distributed environment are getting more complicated as the size of the distributed computing environment grows larger and becomes more dynamic. This thesis proposes an automated framework to manage services in a dynamic distributed environment where the resources available for these services would change from time to time. The aim of this research is to design an automated framework that would continuously search for resources with better performance and pool resources together to achieve better availability using a team formation approach.